Left Ventricular Ejection Fraction Predicts Severity of Posttraumatic Stress Disorder in Patients With Implantable Cardioverter‐Defibrillators. Issue 5 (6th May 2016) - Sawatari, Hiroyuki; Ohkusa, Tomoko; Rahamawati, Anita; Ishikawa, Katsuhiko; Tsuchihashi‐Makaya, Miyuki; Ohtsuka, Yuko; Nakai, Mori; Miyazono, Mami; Hashiguchi, Nobuko; Chishaki, Hiroaki; Sakurada, Harumizu; Mukai, Yasushi; et al.
ABSTRACT: Background: Implantable cardioverter‐defibrillators (ICD) have provided effective therapy for fatal arrhythmia. However, ICD patients are known to develop psychological problems, such as posttraumatic stress disorder (PTSD), if they have experienced potentially fatal arrhythmia and ICD shocks. Little is known about the factors influencing PTSD in ICD patients. Hypothesis: Echocardiographic cardiac‐function parameters might relate to psychological problems, especially PTSD, in ICD patients. Methods: A total of 128 outpatients with ICD implantation completed the Impact of Event Scale Revised (IES‐R) questionnaire as a measurement of PTSD. Demographic and clinical characteristic data were collected from medical records. Results: The mean age of the ICD patients was 59 ± 16 years; 103 were male; and the mean left ventricular ejection fraction (LVEF) by echocardiography was 52.4% ± 18.3%. In the ICD patients, female sex and impaired LVEF were related to lower IES‐R scores or led to PTSD ( P = 0.01 and P = 0.03, respectively). Impaired LVEF also worsened 2 symptoms of PTSD, intrusion ( P = 0.02) and hyperarousal ( P = 0.03). In patients with LVEF <35%, there was a significant negative correlation between LVEF level and IES‐R score ( P = 0.045). Conclusions: This study showed that LVEF was related to the severity of PTSD, especially in the ICD patients with LVEF of <35%. We should pay more attention to ICD patients with severely impaired left ventricular function to prevent psychological problems.